Analysis of standard vs dose-escalated stereotactic body radiation therapy in localized prostate cancer: a comparative evaluation of survival outcomes - Xu, Bichun; Zhao, Xianzhi; Wei, Tingting; Liang, Yiyin; Zhang, Weiwei; Chen, Liang; Lian, Zuping; Zhang, Huojun (Frontiers in Immunology, 2025)
Background and purposeThis study aimed to compare the safety and efficacy of high-dose biologically effective dose (BED) versus standard dose regimens in stereotactic body radiotherapy (SBRT) for localized prostate cancer (PCa) using a propensity score matching (PSM) analysis.MethodsBetween June 2012 and February 2022, prostate-localized SBRT patients from two institutions were retrospectively reviewed. The high-dose group (n=12) received high-dose BED1.5 (>250Gy), and the control group (n=119) according to NCCN guidelines (35-37.5 Gy/5f, BED1.5 198.3-225Gy). PSM was performed in a 1:4 ratio based on key clinical variables. Survival outcomes, including overall survival(OS), cancer-specific survival (CSS), biochemical progression-free survival (bPFS), local control (LC), and distant metastasis-free survival (DMFS)were analyzed using Kaplan-Meier methods with SPSS v26.ResultsIn the 7-year follow-up, the high-dose group exhibited a 66.7% OS rate vs. 83.4% in controls (p=0.402) and an 88.9% CSS rate compared to 90.5% in controls (p=0.480). The high-dose group demonstrated a 91.7% 7-year bPFS rate, while controls had a 67.4% rate (p=0.497). Higher gleason score correlated with impaired biochemical control (p=0.028), and adverse NCCN classifications indicated suboptimal control (p=0.028). The high-dose group achieved a 100% 7-year LC rate vs. 95.1% in controls (p=0.569) and a 91.7% 7-year DMFS rate compared to 81.6% in controls (p=0.918). Patients with pre-existing health conditions were less likely to develop distant metastasis (p=0.047). Most patients tolerated SBRT with minimal toxicity, and no grade 3 or higher adverse events were observed.ConclusionEscalating the biologically effective dose above standard levels did not yield a significant improvement in tumor control or survival outcomes compared to conventional SBRT dosing for localized PCa. Further prospective studies are warranted to clarify the role of dose escalation in this setting.